Application of Polymeric Nanoparticles for CNS Targeted Zinc Delivery In Vivo - Chhabra, Resham; Ruozi, Barbara; Vilella, Antonietta; Belletti, Daniela; Mangus, Katharina; Pfaender, Stefanie; Sarowar, Tasnuva; Boeckers, Tobias M.; Zoli, Michele; Forni, Flavio; Vandelli, Maria Angela; Tosi, Giovanni; et al. (CNS & Neurological Disorders - Drug Targets, 2015)
A dyshomeostasis of zinc ions has been reported for many psychiatric and neurodegenerative disorders including schizophrenia, attention deficit hyperactivity disorder, depression, autism, Parkinson’s and Alzheimer’s disease. Furthermore, alterations in zinc-levels have been associated with seizures and traumatic brain injury. Thus, altering zinclevels within the brain is emerging as a new target for the prevention and treatment of psychiatric and neurological diseases. However, given the restriction of zinc uptake into the brain by the blood-brain barrier, methods for controlled regulation and manipulation of zinc concentrations within the brain are rare. Here, we performed in vivo studies investigating the possibility of brain targeted zinc delivery using zinc-loaded nanoparticles which are able to cross the blood-brain barrier. After injecting these nanoparticles, we analyzed the regional and time-dependent distribution of zinc and nanoparticles within the brain. Moreover, we evaluated whether the presence of zinc-loaded nanoparticles alters the expression of zinc sensitive genes and proteins such as metallothioneins and zinc transporters and quantified possible toxic effects. Our results show that zinc loaded g7 nanoparticles offer a promising approach as a novel non - invasive method to selectively enrich zinc in the brain within a small amount of time.
Keywords: drug delivery